2018
DOI: 10.15288/jsad.2018.79.761
|View full text |Cite
|
Sign up to set email alerts
|

Passing on Pot: High School Seniors’ Reasons for Not Using Marijuana as Predictors of Future Use

Abstract: Marijuana use is relatively common among youth and increases during the transition to adulthood. Ye t a substantial number of adolescents and young adults do not use marijuana. The purpose of this study was to examine how high school seniors' reasons for intending not to use marijuana within the next 12 months were prospectively associated with marijuana use reported 1 year later. Method: Data were drawn from national longitudinal samples of U.S. high school seniors from the Monitoring the Future study (n = 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Given the poor prognosis of substance use disorders for long-term outcomes, direct and indirect screening in medical settings of family members for marijuana use is an important and achievable goal endorsed by the US Preventive Services Task Force . A positive screening result should trigger counseling of parents on risks posed by using and storing marijuana, tobacco, or opioids at home, educating parents on risk and protective factors, and offering reassurances that substance use is modifiable . Reducing marijuana, tobacco, and other substance use by offspring living with a parent using substances is approachable by targeted strategies, such as strengthening families, or with universal prevention approaches that combine mass media campaigns adapted from tobacco cessation campaigns, including school- and community-based programs and changing statewide or community-wide policies and norms …”
Section: Discussionmentioning
confidence: 99%
“…Given the poor prognosis of substance use disorders for long-term outcomes, direct and indirect screening in medical settings of family members for marijuana use is an important and achievable goal endorsed by the US Preventive Services Task Force . A positive screening result should trigger counseling of parents on risks posed by using and storing marijuana, tobacco, or opioids at home, educating parents on risk and protective factors, and offering reassurances that substance use is modifiable . Reducing marijuana, tobacco, and other substance use by offspring living with a parent using substances is approachable by targeted strategies, such as strengthening families, or with universal prevention approaches that combine mass media campaigns adapted from tobacco cessation campaigns, including school- and community-based programs and changing statewide or community-wide policies and norms …”
Section: Discussionmentioning
confidence: 99%
“…The influence of legal factors upon drug use decisions has been demonstrated in students, who reported its criminalised status as a reason for avoiding use in separate Canadian, US and Irish studies (Hathaway et al 2016;Martz et al 2018;Byrne et al 2022). An Australian survey found that the criminalisation of cannabis use was identified as a factor in decisions to avoid or reduce use, these impacts being more prominent in young frequent users ( Weatherburn et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Youth below the poverty line may experience earlier exposure to substance use and substance-related crime, more targeted marketing of substances, and lower parental involvement (Biener & Siegel, 2000;Wills et al, 2004). They may also be more motivated to use substances for reasons beyond stress, such as due to boredom, sensation seeking, and pursuit of enhancing effects in order to compensate for a lack of pleasurable substance-free daily activities (Lee et al, 2018;Martz et al, 2018). Poverty status may similarly influence the types of substances that adolescents use.…”
Section: Poverty Status Differences In Substance Use Motivationmentioning
confidence: 99%